Impact of Fertility and Mowing on Crabgrass Quantity and Quality for Hay Production in Southeast Kansas - D. Helwig; M. Haywood; J. K. Farney; B. C. Pedreira; G. F. Sassenrath (Kansas Agricultural Experiment Station Research Reports, 2021)
A crabgrass variety trial comparing Quick-N-Big and MoJo crabgrasses was conducted during the summer of 2020 at the K-State Research and Extension experiment station near Columbus, Kansas. The trial evaluated quantity and quality of forage produced under different nitrogen fertility scenarios and mowing management techniques. MoJo produced more biomass than Quick-N-Big. Addition of nitrogen fertilizer increased biomass production and forage protein content. Mowing was also found to enhance forage quality.
Keywords: crabgrass; pasture; fertility; biomass production; hay; forage quality; mowing